Genetic Diversity and Population Structure in Bryophyte With Facultative Nannandry - Lang, Annick S.; Gehrmann, Thies; Cronberg, Nils (Frontiers in Plant Science, 2021)
Among plants, gender dimorphism occur in about 10% of all angiosperms and more than 50% of all moss taxa, with dwarf males (DM) found exclusively in some unisexual mosses. In this study, we explore the role of male dwarfism as a reproductive strategy in the widespread acrocarpous moss Dicranum scoparium, which has facultative male dwarfism, having both dwarf males (DMs) and normal-sized males (NMs). We retrieved 119 SNP markers from transcriptomes which were used to genotype 403 samples from 11 sites at seven localities in southern Sweden. Our aims were to compare the genetic variability and genetic structure of sexually reproducing populations at different geographic levels (cushion, site and locality) and compare in particular the relative contribution of females, dwarf males and normal-sized males to the observed genetic diversity. The numbers of DMs differed strongly between sites, but when present, they usually outnumbered both females and NMs. Low genetic differentiation was found at locality level. Genetic differentiation was strongest between cushions for females and NMs and within cushions for DMs indicating small scale structuring and sometimes inbreeding. NMs were more clonal than either DMs or females. Genetic diversity was similar between females and DMs, but lower for NMs. Two haplotypes were shared between females and DMs and one haplotype was shared between a DM and a NM. In conclusion, our results show that DMs and NMs play different roles in reproduction, inbreeding may occur at cushion level, but gene flow is high enough to prevent substantial genetic drift.